POLA KHUTBAH JUM'AT DI KOTA PALEMBANG: PATTERNS OF FRIDAY SERMONS IN PALEMBANG - M Agus Noorbani (Balai Penelitian dan Pengembangan Agama Jakarta, 2014)
Friday sermons (khutbah Jum'at) play a significant role in nurturing the values of faith (iman) and God-consciousness (takwa) among Muslims. This study seeks to explore features of Friday sermons in the City of Palembang, South Sumatera. For the purpose of data collection, researcher with his team attended Friday prayers in 37 mosques during two weeks. The researcher and his team were listening to and recording what Friday sermon preachers delivered. These recorded sermons were then transcribed and analyzed using the method of content analysis. This research found that Islamic faith, noble behavior, and Islamic law were the most popular themes delivered by Friday sermons preachers. However, Friday sermon preachers tended to discuss the themes of their sermons in terms of normative and literal Islamic teachings. Most sermon preachers provided no contextual elaboration of their sermons in order to cope with problems of the Islamic community. They paid less attention to political, economic, and justice issues, as well as science and technology. Key Words: Preaching (dakwah), Friday sermon, mosques, content analysis, Palembang. Khutbah Jum'at memiliki peran yang sangat strategis dalam menanamkan nilai-nilai keimanan dan ketakwaan. Penelitian ini memeriksa pola- pola khutbah Jum'at di Kota Palembang, Sumatera Selatan. Untuk mengumpulkan data, peneliti dengan timnya menghadiri salat Jum'at di 37 masjid selama dua minggu. Peneliti dengan timnya mendengarkan dan merekam pesan-pesan khutbah Jum'at yang disampaikan. Khutbah- khutbah tersebut ditranskripsi dan dianalisis dengan metode analisis isi. Penelitian ini menemukan, bahwa soal-soal keimanan Islam, akhlak terpuji, dan hukum-hukum Islam adalah tema-tema yang populer disampaikan oleh para khatib. Tetapi tema-tema tersebut disampaikan cenderung secara normatif dan lebih menitikberatkan pada penyampaian nilai- nilai Islam tekstual. Banyak khatib yang belum mampu mengelaborasi khutbah Jum'at dengan penjelasan yang kontekstual demi menjawab permasalahan umat. Para khatib kurang memperhatikan tema-tema politik, ekonomi, hukum, serta ilmu dan teknologi. Kata Kunci: Dakwah, khutbah Jum'at, masjid, analisis isi, Palembang.